Exploring barriers of childhood full vaccination among children living in Siraro District, West Arsi Zone, Oromia region, Ethiopia: A qualitative study - Guye, Ararso Hordofa; Nigussie, Tadesse; Tesema, Mengistu; Shambi, Dame Banti; Diriba, Berhanu Senbeta; Tefera, Esayas Mekonen; Girma, Yeabsira (Frontiers in Pediatrics, 2023)
Background: Childhood immunization is one of the most effective public health interventions to reduce childhood morbidity and mortality. However, some children remain not full vaccinated in developing countries due to defaulting from vaccination that can put the children at risk of acquiring vaccine preventable disease and the barriers of full vaccination is not well-explored in Ethiopia using qualitative approach. The aim of this study was to explore barriers of childhood full vaccination in Siraro District, West Arsi Zone, Oromia, Ethiopia. Methods: A Qualitative study was conducted in Siraro District with 15 key informant health workers and 6 in-depth interviews with child mothers from April 20 to May 15, 2022. Data were collected using semi structured questionnaires and captured using audio tape recorders and field note taking. The heterogeneous purposive sampling technique was used to select representative study participants. Data transcription and translation were done according to verbatim of respondents from local language to English. Data coding and key categories were identified and analyzed using thematic analysis. Then presented in narrative forms using respondents own words as an illustration. Result: Twenty-one participants were interviewed and included in this study. Of the explored barriers of full vaccination the evidence from the respondents were integrated from sub categories and presented as a whole within each themes and five thematic area were emerged from interviews of the participants. The identified barriers were forgetting vaccination schedule, migration of parents, work overload, lack of knowledge and awareness, rumours, misinformation. Additionally, vaccination service delivery barriers such as vaccine vial not opened for few children, fear of side effects, closed health post during visit, absence of health extension workers at the health post were the key barriers of childhood full vaccination. Conclusion: Forgetting vaccination schedule, migration of parents, work overload, rumours, misinformation, fear of side effects, vaccine vial not opened for few children, closed health post during visit, absence of health extension workers from health post were the key barriers of full vaccination. Thus, the district health office should work on barriers of full vaccination by strengthening vaccination service and improving awareness on vaccination through health extension program.